High-sensitivity C-Reactive Protein is a Prognostic Biomarker of 6-month Disability After Traumatic Brain Injury: Results from the TRACK-TBI Study. (16th November 2020) - Yue, John K; Xu, Linda; Korley, Frederick; Puccio, Ava; Yuh, Esther; Sun, Xiaoying; Rabinowitz, Miri; Vassar, Mary J; Taylor, Sabrina; Winkler, Ethan A; Puffer, Ross; Deng, Hansen; et al.
Abstract: INTRODUCTION: Systemic inflammation impacts outcome after traumatic brain injury (TBI), but most TBI biomarker studies have focused on brain-specific proteins. C-reactive protein (CRP) is a widely used biomarker of inflammation with potential as a prognostic biomarker after TBI. METHODS: The Transforming Research and Clinical Knowledge in Traumatic Brain Injury (TRACK-TBI) study prospectively enrolled TBI patients within 24h of injury, as well as orthopedic injury and uninjured controls; biospecimens were collected at enrollment. A subset of hospitalized participants had blood collected on day 3, day 5, and 2 weeks. High-sensitivity CRP (hsCRP) and glial fibrillary acidic protein (GFAP) were measured. Receiver Operating Characteristic analysis was used to evaluate the prognostic ability of hsCRP for 6-month outcome, using the Glasgow Outcome Scale-Extended (GOSE). RESULTS: We included 1206 TBI subjects, 122 orthopedic trauma controls (OTC), and 209 healthy controls (HC). Longitudinal biomarker sampling was performed in 254 hospitalized TBI subjects and 19 OTCs. hsCRP rose between days 1–5 for TBI and OTC subjects, and fell by 2 weeks, but remained elevated compared with HC ( P < . 001). Longitudinally, hsCRP was significantly higher in the first 2 weeks for subjects with death/severe disability (GOSE < 5) compared with those with moderate disability/good recovery (GOSE ≥ 5); AUC was highest at 2 weeks (AUC = 0.892). Across all timepoints, hsCRP rose with increasing Injury Severity Score (ISS). Combining hsCRP and GFAP at 2 weeks produced AUC = 0.939 for prediction of disability. CONCLUSION: Serum high-sensitivity CRP measured within 2 weeks of TBI is a prognostic biomarker for disability 6 months later. hsCRP may have utility as a biomarker of target engagement for anti-inflammatory therapies.